Impact of Sample Storage Time and Temperature on the Stability of Respiratory Viruses and Enteric Viruses in Wastewater - Judy Y. Qiu; Richardson Mah; Logan A. Brand; Xiaoli Pang; Melodie Barnett; Mathew Diggle; Graham Tipples (Microorganisms)
Wastewater-based surveillance (WBS) has been widely used to track SARS-CoV-2 as well as many other viruses in communities during the COVID pandemic and post-pandemic. However, it is still not clear how temperature and storage time would influence the stability of viruses in wastewater. In this study, we assessed the stability of SARS-CoV-2, pepper mild mottle virus (PMMoV), influenza viruses A (IAV) and B (IBV), respiratory syncytial virus (RSV), and enteric viruses in raw wastewater stored at room temperature, 4 °C, and −20 °C for 3 and 6 days. SARS-CoV-2, PMMoV, IAV, and enteric viruses were found to be stable up to 6 days after storing at room temperature or 4 °C. SARS-CoV-2 and RSV were more susceptible to freeze–thaw cycles compared to PMMoV and enteric viruses, which were relatively stable for up to 6 days stored at −20 °C. Low detection of IBV in wastewater made it difficult to evaluate the impact. Based on our findings, we conclude that short-term storage or transportation of wastewater samples within 6 days at ambient temperature or 4 °C is acceptable for the majority of these viruses. Freezing samples at −20 °C for even short periods is not recommended for WBS of respiratory viruses. The data obtained from this study can provide guidance for quality assurance purposes from the operational aspects of wastewater surveillance.